2016
DOI: 10.1007/s00296-016-3423-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment persistence among patients with immune-mediated rheumatic disease newly treated with subcutaneous TNF-alpha inhibitors and costs associated with non-persistence

Abstract: The main objective of this study was to describe real-world treatment persistence with subcutaneous tumor necrosis factor-alpha inhibitors (SC-TNFi) in patients with ankylosing spondylitis, psoriatic arthritis, or rheumatoid arthritis [collectively immune-mediated rheumatic disease, (IMRD)] in Sweden. A secondary objective was to describe potential effects on health care resource utilization (HCRU) cost from non-persistence. Patients were identified through filled prescriptions for adalimumab (ADA), etanercept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 18 publications
7
68
1
1
Order By: Relevance
“…1a). This definition of persistence was consistent with that employed in other claims data-based studies of RA [10, 26] and other indications [27, 28].
Fig.
…”
Section: Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…1a). This definition of persistence was consistent with that employed in other claims data-based studies of RA [10, 26] and other indications [27, 28].
Fig.
…”
Section: Methodssupporting
confidence: 87%
“…The Swedish study reported that persistence was associated with a cost savings of US$987, while non-persistence led to a cost increase of US$793 [10]. Of note, the cost of the bDMARDs was not included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, five studies were excluded on the basis that they presented persistence estimates from the same, or partially the same, patients from the same data source as other studies 28–32. Therefore, a total of twelve references were included in the review 20,33–43Figure 1 provides a description of the flow of information during the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 provides a description of the flow of information during the selection process. Among the twelve references, all presented proportions of patients on golimumab at reported follow-up(s), and one reported median time to 50% of patients being nonpersistent 33. Five studies compared persistence to golimumab with persistence to other TNFis 20,33,34,36,38…”
Section: Resultsmentioning
confidence: 99%